(untitled) (Lex localis - Journal of Local Self-Government, 2020)
At the turn of the 21st century, we witnessed a civilisational change that resulted in decentralisation and deconcentration of power. As a result, international cooperation between local authorities has increased. This article is to indicate the legal basis for international local government activities, forms of cooperation and their impact on regional development. The legal bases for this cooperation can be classified as follows: 1. Sources of public international law, 2. EU Community law, 3. Sources of national law. Having this in mind, the article will discuss the selected legal bases for international self-government activity in Europe, starting with the acquis of the Council of Europe, then moving on to the activities of the European Union. Finally, an analysis of forms of international cooperation of local government units in Poland are going to be presented. These considerations are largely of a theoretical nature, based in particular on jurisprudential analysis.